Self-Healing Hydrogels Based on Sodium Carboxymethyl Cellulose/Poly(vinyl alcohol) Reinforced with Montmorillonite - Nicharee Weerawan; Jongjit Chalitangkoon; Pathavuth Monvisade (My University, 2021)
Currently, self-healing hydrogels prepared from the green process have been studied for various applications, especially in the biomedical field. This work fabricated the self-healing hydrogel based on sodium carboxymethyl cellulose/poly(vinyl alcohol)/montmorillonite by acidifying the mixture with citric acid. SEM measurements showed well-dispersed montmorillonite in the hydrogels. Cytotoxicity values >100% were seen with montmorillonite added, which indicated cell growth and no cell toxicity. Montmorillonite addition not only reinforced the networks but also improved self-healing ability. The tensile strength of the original uncut hydrogel with montmorillonite (P1C8M1) was 61 kPa, whereas the healed hydrogel showed 57 kPa. The hydrogel healed completely within 10 days, without any cracks, i.e., a 93% healing efficiency, or higher than the ~60% of the non-reinforced hydrogel. This confirmed strong hydrogen bond formation between the polymer and montmorillonite. The self-healing ability of this non-toxic hydrogel, reinforced with montmorillonite, makes it valuable for use in biomedical fields.
Keywords: Carboxymethyl cellulose; Vinyl alcohol; Hydrogels: synthesis, properties, applications